2020
DOI: 10.1155/2020/2862917
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Land Surface Temperature Driving Factors and Spatial Heterogeneity Research Based on Geographically Weighted Regression Model

Abstract: Acceleration of urbanization has brought about a series of problems, which include irreversible changes to urban surfaces and continuous increases in land surface temperatures (LSTs). In this context, analysis of the driving factors and spatial heterogeneity of urban LST is of considerable importance for mitigating urban heat island effects and promoting healthy and comfortable urban living environments. This study explored the relationship between the spatial characteristics and driving factors of the LST by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The results obtained indicated a similarity to those of the study of Phan et al [64], which was conducted in a mountainous region of Vietnam when both MODIS and Landsat datasets were averaged as well. Rising temperatures not only cause hardships for agriculture but also negatively impact the tourism sector [64][65][66].…”
Section: Topographical Relationship To Lst and Lulccmentioning
confidence: 99%
“…The results obtained indicated a similarity to those of the study of Phan et al [64], which was conducted in a mountainous region of Vietnam when both MODIS and Landsat datasets were averaged as well. Rising temperatures not only cause hardships for agriculture but also negatively impact the tourism sector [64][65][66].…”
Section: Topographical Relationship To Lst and Lulccmentioning
confidence: 99%
“…The correlation coefficient between NDVI and LST also indicates strong negative influences on LST dynamics. Previous studies have confirmed the significant inverse influences of water and vegetation dynamics on surface temperature ( Zhi et al., 2020 ). The positive correlations between the NDBAI and LST (Pearson's r = +0.4643, +0.4899 and +0.47701) indicate that the increase of bare lands has been accelerating the surface temperature of Dhaka.…”
Section: Resultsmentioning
confidence: 62%
“…The results show that the interactions between MNDWI, IBI, and NDVI were the main factors influencing the variations of Wuhan's LST in each season. Previous studies [43,[87][88][89] have confirmed that physical factors such as water and vegetation play an important role in mitigating SUHI by using the remote sensing index (MNDWI and NDVI). Similarly, there is no hightemperature agglomeration in Wuhan's water area and forest land.…”
Section: Effects Of Impact Factors On Lstmentioning
confidence: 88%
“…With the acceleration of urbanization and industrialization, the influence of socioeconomic factors on LST variations is becoming more and more important [88,91]. The impact of socio-economic factors, such as anthropologic heat releases and build-up intensity, on the spatial distribution pattern of SUHI were confirmed in China's 32 major cities [92].…”
Section: Effects Of Impact Factors On Lstmentioning
confidence: 96%